Pengaruh Pemberian Kinesio Taping Dan Core Stability ExerciseTerhadap Penurunan Nyeri Pada Low Back Pain Myogenic Petani - Prasetyo, Rian; , Wijianto M.OR; , Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: Lower back pain or low back pain myogenic is pain around of the lower back mucle or a disorder caused byabnormalities in the muscles and tendons of elements without neurologicaldisorders. Low back pain may result in pain, muscle spasm and muscleimbalance Low back pain myogenic can be occurred in farmer because bent positionfor a long time. Kinesio tapping and core stability exercise can relieve pain low back pain myogenic cases. Purpose of the research. To knowing the effect and difference of effect between kinesio taping and core stability exercise on pain relieving of low back pain myogenic. Method of the research: It is a quasi-experimental research with pre and post test two group design. Population of the research was workers of farmer at BotoVillage. Respondents who had criteria of inclusion were 20 respondents aged 55-65 years, they were divided to be an kinesio tapping group (10 respondents) and a core stability exercise group (10 respondents). Pain was measured using a visual analog scale (VAS). Data were analyzed using Wilcoxon test to test the influence and Mann Whitney test to test different influences. Results of the Research: There is a positive effect on pain reduction kinesio taping and core stability exercise oflower back pain or low back pain myogenic after using a statistical test p-value obtained wicoxon on silent pain (ND), tenderness (NT) and the pain of motion (NG) 0,005 in the kinesio taping and core stability exercise group, and statistical mann withneyon silent pain (ND) and tenderness (NT) did not have a significant difference, but the pain of motion (NG) indicated p value = 0,044< 0,05 Conclution: At the pain of motion (NG), there is significant difference of effect between kinesio tapping group and core stability exercise group on alleviation of low back pain. Key Words : Kinesio Taping, Core Stability Exercise, Low Back Pain Myogenic